Case Reports Case reportTracheal cancer treated with a short course of external and endoluminal radio-chemotherapy combined with cetuximab – a case report - Papadopoulou, Aikaterini; Froudarakis, Marios; Abatzoglou, Ioannis; Koukourakis, Michael I. (Journal of Contemporary Brachytherapy, 2010)
Primary tumors of the trachea are rare. Such cases are presented with acute respiratory distress demanding immediate therapeutic intervention. Herein, we present a case of an unresectable second primary tracheal cancer treated with intraluminal brachytherapy (8 Gy at 1 cm from catheter) followed by a short course of external beam hypofractionated radiotherapy (4.5 Gy × 4 fractions) and a final brachytherapy fraction (8 Gy), delivering a biological dose higher than 57.5 Gy (for / = 4 Gy) to the tumor within 4 weeks. Concurrent chemotherapy consisted of: fluoruracil (1000 mg/m 2 ), leucovorin (100 mg/m 2 ), oxaliplatin (80 mg/m 2 ) and cetuximab (500 mg/m 2 ), administered every two weeks for two consecutive cycles. Complete response was evident during the second brachytherapy fraction and the patient is alive with no evidence of disease, two years after therapy, without any late radiation sequel.